Linden Hills: Saga of undiluted suffering - Rashmi, Rashmi (Linguistics and Culture Review, 2022)
Linden Hills by Gloria Naylor marks psychological fragmentation which results into immense pain and suffering. Naylor, in this novel, addresses the physical and mental hierarchies which act as blockades in the higher purpose of human integration. This paper aims to investigate the saga of undiluted suffering in the lives of women in Linden Hills. The novelist shows in true colors how the black women become sacrificial lambs and receive the brunt of the frustration of the black males of their society. This paper is also a close study of black males mentality when they get unbridled power and exert it on all those who are subversive to them. Women become the easy victim of their ruthless power play. The tragedy is more intense because the women have been suffering for many generations. In every generation, Nedeed male marries a light-complexioned woman just to reduce her to a child-bearing tool. Failing that, the woman has to lead a life full of hardships and depravity. This paper analyses how her loud desires to stand against the institutionalized trauma herald a new era of freedom from pain and suffering.